Wind Engineering 1980
DOI: 10.1016/b978-1-4832-8367-8.50056-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Wind Tunnel and Full-Scale Building Surface Pressures With Emphasis on Peaks

Abstract: sufficient full-scale data exist. A method of treating peak pressures is proposed based on the fit of an exponential distribution to a population of "significant independent events, " called pressure spikes. This distribution provides a good fit to both full-scale and wind tunnel results, which generally agree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…They found that the observed building movements and wind tunnel results correlated well once the model data had been adjusted for building frequencies. In 1979, Dalgliesh et al [29] compared the full-scale wind pressure coefficients measured from that 57-storey building with the corresponding model test data. A good agreement was shown where sufficient full-scale data were employed.…”
Section: Dalgliesh's Full-scale/model Test Comparisonsmentioning
confidence: 99%
“…They found that the observed building movements and wind tunnel results correlated well once the model data had been adjusted for building frequencies. In 1979, Dalgliesh et al [29] compared the full-scale wind pressure coefficients measured from that 57-storey building with the corresponding model test data. A good agreement was shown where sufficient full-scale data were employed.…”
Section: Dalgliesh's Full-scale/model Test Comparisonsmentioning
confidence: 99%